'Closing the gap': Evaluating the success of non-mandatory strategies for influenza vaccination of Victorian healthcare workers. Issue 41 (22nd September 2020) - Bennett, N.; Crouch, S.; Hoskins, A.; Malloy, M.J.; Walker, K.; Worth, L.J.
Abstract: Introduction: While annual influenza vaccination of healthcare workers (HCWs) is recommended, uptake is often suboptimal. We sought to evaluate influenza vaccination uptake by HCWs in Victorian public healthcare facilities, where non-mandatory programs are used. Methods: All participating facilities completed an annual survey (2014–2019) recording HCW influenza vaccination status. Uptake in high-risk departments (emergency and intensive care units) was evaluated for the 2019 season. Results: The proportion of vaccinated HCWs increased annually, from 72.2% (2014) to 87.7% (2019), with pre-set targets generally achieved. In 2019, 110, 324 HCWs in 107 facilities were vaccinated (87.7%). Of those without documented vaccination, 7591 (6.0%) declined and 7906 (6.3%) had unknown status. Uptake was higher in high-risk departments (91.4%). Conclusion: Increasing annual influenza vaccination uptake by HCWs in Victorian public healthcare facilities has been achieved in the context of performance monitoring targets. Small proportions declined or had unknown status. Future policies should focus on these HCWs.